Kepuasan Pasien terhadap Aplikasi Pendaftaran Online Menggunakan Metode EUCS (End User Computing Satisfaction) di RSUP Fatmawati - Rumana, Nanda Aula; Putra, Daniel Happy; Widjaja, Lily; Noviandi, Noviandi; Maharami, Iradah; Hidayat, Rahmat (Journal of Hospital Management, 2021)
Online registration is one application that can reduce queues at the hospital. However, its application must meet the standards so that patients are satisfied with the online registration application. This research was conducted to determine the description of patient satisfaction with online registration applications using end user computing statisfaction. Samples obtained in this study were 73 respondents taken by incidental sampling. The design of this study is cross sectional where research is only measured one time to find out the picture of satisfaction. The level of patient satisfaction is measured using the EUCS (End User Computing Statisfaction) model which consists of five components namely content, accuracy, format, ease of use and timeliness. Data in this study were obtained from questionnaires to patients or families of patients who registered through the online registration application. The results showed that of 73 respondents 45 respondents (61,6%) were dissatisfied and 28 respondents (38,4%) were satisfied. This study concludes that there are still many patients or users who feel unsatisfied with the online registration application. Suggestions aimed at online registration applications are to design the interface on the application so that it is more user friendly, reducing errors during data processing, updating the doctor's schedule, speeding up access when registering online and speeding up the process of downloading barcodes on the online registration application.Keywords: Online registration, satisfaction, content, accuracy, format, ease of use and timeliness.